Mouth to Mouth: Queer Desires in Emma Donoghue's Kissing the Witch. - Orme, Jennifer (Marvels & Tales, 2010)
This reading of Emma Donoghue's Kissing the Witch attempts to magnify the "queer moments," textual and formal, that any reader may (or may not) notice and (re)focus them so that their disruptions come to the fore, thus realigning the relationship between reader and text. Ideally, this reading process will contribute to an understanding of how Kissing the Witch, in conjunction with its reader, can be said to queer fairy tales. This article assumes that once such a reading is produced, it becomes easier to produce, if not more difficult to avoid, similar readings of Kissing the Witch's intertexts and, by extension, the fairy-tale genre itself.